Humanização na atenção básica: percepção de usuários, profissionais e gestores - Barros, Ana Stella Achoa (2018)
Within any health care system, as is the brazilian unified health care system – Sistema Único de Saúde (SUS), all health care acts are composed of technical aspects, properly constituted by the procedures, and by non-technical aspects, intrinsic to the meeting of two people, in the relationship between professional and patient. These last aspects are closely related to the humanized attitudes within health assistance. The aim of this study was to carry out a survey of the humanization applied in Health Assistance, in the Basic Health Care Units (BHUs) of Bauru, State of São Paulo, in order to provide data to municipal managers, who are able to collaborate for improvements, if necessary. Material and Method: a survey was conducted collecting data about the perception of users, professionals and managers, regarding the presence of humanization in their practices, at three UBSs of the Bauru city. The data collection instrument was composed of: adaptation of a questionnaire developed and validated by the World Health Organization to measure Responsiveness (how much of non-technical aspects the Health System is able to provide). This questionnaire was applied to the subjects, with supervision of the researcher. The results were presented by means of the absolute frequency (n), relative frequency (%), average and the comparison between the classes of participants and between health units, using the Student t test, ANOVA (Analysis of Variance), Tukey test, paired, when possible, adopting a significance level of 5%. It was recorded that, Health Care System Responsiveness was well rated, although, only for the area of Confidentiality, the presence of Humanization, was indicated in the three units studied. The presence of Dignity and Communication was found only in two of the BHUs studied, one of them showed a deficit, in terms of listening and time for questioning. The domains/ aspects that presented flaws in all UBSs were: Autonomy, Prompt Attention, Quality of Working Structure, Choice of Care Provider and Management Council. One of the units, by the perception of users, proved to be better than others, for all the questions from all the domains studied, where Humanization was present. In the aspects related to the health care professionals, some Participative Management was present. For all aspects, professionals revealed a deficit, related to a same unit. By the perception of the managers, Humanization deficits occurred, differently, in each unit studied, for the following aspects: Construction of Tasks and Participative Management; existence of an Expanded Clinic and time for Linking between Professionals. It is concluded that the municipality still has a Humanization deficit, lower in some UBSs than in others. For full development, the use of the devices, suggested by the National Humanization Policy, could bring innumerable benefits, among them the implantation of Working Groups in Humanization, at the UBSs.